Food Colonialism and Social Media: Multimodal Discourse Analysis of "Food Barter" Content on Instagram (Architecture Image Studies, 2026)
The research analyzes food colonialism practices through the "food barter" content posted by @wikeafrilia on Instagram, using the multimodal discourse analysis approach of Gunther Kress and Theo van Leeuwen. The method employed is qualitative interpretative, focusing on four communication strata: discourse, design, production, and distribution. The findings indicate that in the discourse, the minor impression and food colonialism towards the Papuan community are influenced not only by state policies but also by the "food barter" content that makes the community dependent on rice and instant noodles, rather than local food. In the design, the choice of genre highlighting poverty reinforces the minor impression of the local community, creating a classification between those deemed modern and primitive. In the production stage, the use of various semiotic modes such as text; titles, moving text, material resources, instrumental music, and colors; black and white, articulates food colonialism practices. For example, material resources like rice and instant noodles are consistently a vital part of every content, with their frequency surpassing local food items that are bartered, such as sago or tubers. In the final stage, distribution, Instagram is used for meaning dissemination. This is not only because Instagram offers various features that can be utilized, but also because it is the most widely used platform.